X-ray spectroscopic study of structural isotypism in Me₂Si silicides - Gel, P.V.; Yushchenko, A.V.; Nedybalyuk, A.F.; Sakhno, V.M. (Functional Materials, 2004)
Basing on consideration of the shape, width, energy position, and integral intensity of X-ray spectra of all series as well as of photoemission quantum yield, an attempt has been made to explain the isotypism nature for silicides of transition metals belonging to the beginning and end of the 1st large period. На основании формы, ширины, энергетического положения и интегральной интенсивности рентгеновских спектров всех серий, а также квантового выхода фотоэмиссии сделана попытка объяснить природу изотипизма силицидов переходных металлов начала и конца первого большого периода. На основі аналізу форми, ширини, енергетичного положення та інтегральної інтенсивності рентгенівських спектрів усіх серій, а також квантового виходу фотоемісії зроблено спробу пояснити природу ізотипізму силіцидів перехідних металів початку і кінця першого великого періоду.